OS 19-01 BLOOD PRESSURE INDEPENDENT EFFECTS OF RENAL DENERVATION ON THE DECLINE OF KIDNEY FUNCTION IN PATIENTS WITH CHRONIC KIDNEY DISEASE. (September 2016) - Hering, Dagmara; Marusic, Petra; Duval, Jacqueline; Sata, Yusuke; Esler, Murray; Walton, Antony; Schlaich, Markus
Abstract : Objective: Previous studies have shown that renal denervation has the potential to reduce blood pressure (BP) and slow the decline of renal function in chronic kidney disease (CKD) patients up to 12 months post procedure. The effects of RDN on estimated glomerular filtration rate (eGFR) and BP reduction beyond the first year remain unknown. This study investigated the effects of RDN on renal function and BP in CKD patients (eGFR ⩽ 60 ml/min/1.73 m 2 ) out to 24 months post procedure. Design and Method: eGFR from the previous 60 months were retrospectively collected from 46 CKD patients who were scheduled for RDN. eGFR and 24-hour ABPM was prospectively assessed at baseline, 3, 6, 12 and 24 months after RDN. Results: A significant reduction in eGFR was noted from months 60 to 48 (-7.3 ± 8.7), months 48 to 36 (−1.4 ± 8.6), months 36 to 24 (−2.7 ± 6.0), months 24 to 12 (−5.9 ± 7.9 ml/min/1.73m 2 ) (P < 0.001), and from 12 months to baseline prior to RDN by −3.4 ± 7.9 ml/min/1.73 m 2 (P < 0.01). RDN improved eGFR at 3 months (+3.7 ± 6.7 ml/min/1.73 m 2 ), 6 months (+2.7 ± 9.0 ml/min/1.73m 2 ) and 12 months follow-up (+1.8 ± 10.8 ml/min/1.73m 2 ) with only a small decline of −1.2 ± 11.3 ml/min/1.73 m 2 at 24 months follow-up (P < 0.05). There was no significant change in daytime SBP between visits from baseline to 12 months after RDN for the entire cohort. Patients with baseline daytime SBP  >  135 mmHg (n = 12) experienced a significant reduction in daytime SBP 24 months post procedure (P = 0.009). Changes in daytime BP were unrelated to the changes in eGFR at 6 months (r = 0.033, P = 0.84), 12 months (r = 0.01, P = 0.93) and 24 months (r = −0.42, P = 0.17) follow-up. Conclusions: Our findings indicate that RDN slows further progression of renal function irrespective of BP lowering effects in patients with CKD. The improvement in eGFR post procedure may be associated with alterations of intrarenal and glomerular haemodynamics achieved with RDN via inhibition of sympathetic outflow to the renal vasculature.